THE EFFECT OF NBF (Neutral Buffered Formalin) 10% EARLY FIXATION ON UTERINE MESENCHYMAL CELL MORPHOLOGY IN A SIMPLE LABORATORY - Rahmi, Mawar; Hutasoit, Gina Andyka; Fitriani, Junjun; Basry, Amirah (Universitas Tadulako, 2026)
An unoptimal duration of tissue fixation can cause degradation of cell morphology and reduce the accuracy of histopathological diagnosis. This study examined the effect of fixation duration using 10 percent Neutral Buffered Formalin on the morphology of uterine mesenchymal cells. The objective was to identify and compare their morphological characteristics after fixation for less than 2 weeks and more than 2 weeks and determine the optimal duration. A quasi-experimental design used 56 uterine leiomyoma samples divided into 2 fixation groups and processed with standard histopathology procedures using hematoxylin eosin staining. Morphological quality was evaluated based on nuclear color, cytoplasm, and cell membrane clarity using a 6-level assessment. Data were analyzed with descriptive statistics and a nonparametric comparative test. The group fixed for less than 2 weeks showed higher morphological values than the group fixed for more than 2 weeks, demonstrating clearer smooth muscle fibers, nuclei, and cytoplasm, while prolonged fixation produced shrunken nuclei and denser cytoplasm with reduced clarity. These findings indicate that fixation duration significantly influences the morphological quality of uterine mesenchymal cells, and fixation for less than 2 weeks yields superior morphology. This emphasizes the importance of appropriate fixation duration for producing reliable histopathological preparations.